2012
DOI: 10.1158/0008-5472.can-11-4058
|View full text |Cite
|
Sign up to set email alerts
|

VEGF Exerts an Angiogenesis-Independent Function in Cancer Cells to Promote Their Malignant Progression

Abstract: Vascular endothelial growth factor/vascular permeability factor (VEGF/VPF or VEGF-A) is a pivotal driver of cancer angiogenesis that is a central therapeutic target in treatment of malignancy. However, little work has been devoted to investigating functions of VEGF that are independent of its pro-angiogenic activity. Here we report that VEGF produced by tumor cells acts in an autocrine manner to promote cell growth through interaction with the VEGF receptor neuropilin-1 (NRP-1). Reducing VEGF expression by tum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
96
2
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(102 citation statements)
references
References 19 publications
1
96
2
3
Order By: Relevance
“…It is widely accepted that the higher the expression levels of VEGF-A mRNA, the poorer the breast cancer prognosis (Linderholm et al, 2000). VEGF-A is a pivotal driver of cancer angiogenesis and considered an important therapeutic target in the treatment of malignancy (Cao et al, 2012). The expression of VCAM-1 has been closely associated with oncogenesis, tumor angiogenesis and metastasis in cancer (Ding et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It is widely accepted that the higher the expression levels of VEGF-A mRNA, the poorer the breast cancer prognosis (Linderholm et al, 2000). VEGF-A is a pivotal driver of cancer angiogenesis and considered an important therapeutic target in the treatment of malignancy (Cao et al, 2012). The expression of VCAM-1 has been closely associated with oncogenesis, tumor angiogenesis and metastasis in cancer (Ding et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the growth and progression of lymphomas are mediated by two mechanisms: autocrine stimulation of tumor cells via the expression of VEGF and its receptors by neoplastic cells, and the paracrine effect of a pro-angiogenic tumor microenvironment (CAO et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is believed that VEGF may act in tumorigenesis, regardless of angiogenesis and lymphangiogenesis (SENGER, 2010; PERROT-APPLANAT; DI BENEDETTO, 2012;CAO et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, neuropilin-1 (NRP-1, NP-1) a semaphorine receptor involved in axon guidance during brain development [34,35] has been shown to play a role in angiogenesis-independent malignant progression [36] by increasing the affinity of various VEGF ligands to the primary VEGF-receptors. Cariboni et al were also able to illustrate a KDR and blood vessel independent way via VEGF-NRP-1 interactions [37].…”
Section: Identification Of Key Angiogenic Factorsmentioning
confidence: 99%